ANALYSIS OF EDUCATIONAL ADMINISTRATION MANAGEMENT PROBLEMS AT KELAPA DUA PUBLIC ELEMENTARY SCHOOL - Faisal Achmad Narahaubun (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
This study aims to determine how the Administration Management, the Effectiveness of the management of educational administration management and the Supporting and Inhibiting Factors. The data successfully collected in this study were analyzed using descriptive qualitative analysis techniques through steps, or components of interactive model data analysis. The data collection techniques used in this study were interviews, observations and documentation. The research informants were determined through purposive sampling techniques, where, against parties who were considered close and knew directly the data and information regarding the problem of Educational Administration Management at SD Negeri Kelapa Dua, totaling 7 people. Qualitative descriptive analysis techniques were used to analyze the data. The results of this study indicate that the effectiveness of management, the effectiveness of supervision of educational administration management are in fairly good condition, this is supported by local government policy factors, and HR factors, Budget factors and facilities and infrastructure factors are in fairly good condition.